EDUCATOR’S STRATEGY FOR DEVELOPING CREATIVITY IN CHOIR TRAINING - Narindra Qonita; Indrar Sabri; Setyo Yanuartuti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
Art education has a huge impact on the development of students’ creativity. In choir training, teachers must also have creativity in conveying learning material so that they can produce good-quality choral groups. The research purpose of this paper is to explain the function of art creativity, the implementation of music and choir learning in schools, and choir training strategies as a means of developing creativity. The research uses a qualitative approach with a descriptive conceptual analysis method. The research uses a conceptual analysis method that examines various literature related to the research objectives. The data analysis techniques are carried out through data reduction, data presentation, and data analysis. The results of data analysis indicate that the art of music education and choir training can be a means of developing creativity for the art performers, either students or teachers. Choir training can encourage students to be creative in expressing the song that is sung. Therefore, it is essential for teachers who have knowledge and skills to seek learning strategies in choir arts to develop students' creativity.